La Lectura Comprensiva y el Desarrollo del Pensamiento Crítico, de los niños de tercer año de Educación Básica de la Unidad Educativa “Simón Bolívar”, del Cantón Riobamba, Provincia de Chimborazo, Período 2014 -2015 - Jaya Hernández, Mery Azucena (2016)
This research originated from the need to develop critical thinking in children of the third year of basic education of the Educational Unit “Simon Bolivar” in the city of Riobamba. At this level it is known the limiting treatment of reading comprehension by the teacher. There is general and specific objective, among them are raised: to determine the contribution of reading comprehension in the development of critical thinking of children in third grade of the Educative Unit Simón Bolívar in Riobamba County, of Chimborazo province, 2014 2015. To come to fulfillment we started from analysis of a theoretical framework emphasizing the approach of the two variables with their respective sub- study. A hypothesis that it is checked by the proportional method was established. Regarding the methodological framework a non-experimental design was used because is was not manipulated any variable, the type of research was exploratory, descriptive and explanatory so we can relate the reading comprehension and the development of thought; the method that prevailed was the scientist who guide all the work allowed to pass on to the truth. The general methods were inductive, deductive, analytical and synthetic that are evident in each of the chapters. The technique was put in operation the same observation that provided the information required finding relevant findings; the instrument was the observation sheet with 12 items, the same that was valued by experts in science. It finally came to the conclusion that comprehensive reading helps develop thinking in children; therefore it corresponds to the teacher to seek methodological strategies to find a better participation and creativity in students.